A small variation in average particle size of PLGA nanoparticles prepared by nanoprecipitation leads to considerable change in nanoparticles' characteristics and efficacy of intracellular delivery. (17th November 2017) - Sahin, Adem; Esendagli, Gunes; Yerlikaya, Firat; Caban-Toktas, Secil; Yoyen-Ermis, Digdem; Horzum, Utku; Aktas, Yesim; Khan, Mansoor; Couvreur, Patrick; Capan, Yilmaz
Abstract: In this study, it was aimed to investigate characteristics and intracellular delivery of two different-sized PLGA nanoparticles in ouzo region by considering number of nanoparticles. To determine the effect of formulation parameters on average particle size, Dil labeled nanoparticles were prepared using a three-factor, two-level full factorial statistical experimental design. PLGA230 (230.8 ± 4.32 nm) and PLGA160 (157.9 ± 6.16 nm) nanoparticles were obtained by altering polymer amount based on experimental design results and characterized. Same number of PLGA230 and PLGA160 nanoparticles per cell were applied onto HEK293 cells; then, cytotoxicity, uptake kinetics and mechanism were evaluated by flow cytometry and fluorescent microscopy. Also same weight of PLGA230 and PLGA160 nanoparticles were applied and cellular uptake of these nanoparticles was evaluated. It was found that PLGA230 nanoparticles had higher encapsulation efficiency and slower dye release compared to PLGA160 nanoparticles. When they were applied at same counts per cell, PLGA230 nanoparticles displayed faster and higher intracellular dye transfer than PLGA160 nanoparticles. On the other hand, PLGA160 appeared to be a more effective vehicle than PLGA230 when applied at the same weight concentration. It was also shown that for both nanoparticles, HEK293 cells employed macropinocytic, caveolae- and clathrin-mediated endocytic pathways.